Socioeconomic per-case costs of stroke, myocardial infarction, and preterm birth attributable to air pollution in Sweden - Kriit, Hedi; Sommar, Johan Nilsson; Åström, Stefan (PLOS ONE, 2024)
Background Incident cases of stroke, myocardial infarction, and preterm birth have established exposure-response functions associated with air pollution. However, there are no studies reporting detailed costs per case for these health outcomes that are adapted to the cost-benefit tools that guide the regulation of air pollution. Objectives The primary objective was to establish non-fatal per-case monetary estimates for stroke, myocardial infarction, and preterm birth attributable to air pollution in Sweden, and the secondary objective was to ease the economic evaluation process of air pollution morbidity effects and their inclusion in cost-benefit assessments. Methods Based on recommendations from the literature, the case-cost analysis considered direct and indirect medical costs, as well as production losses and informal costs relevant for the calculation of the net present value. A literature search was conducted to estimate the costs of each category for each incident case in Sweden. Informal costs were estimated using the quality-adjusted life-years approach and the corresponding willingness-to-pay in the Swedish population. The total average per-case cost was estimated based on specific health outcome durations and severity and was discounted by 3.5% per year. Sensitivity analysis included varying discount rates, severity of health outcome, and the range of societal willingness to pay for quality-adjusted life years. Results The average net present value cost estimate was €2016 460k (185k-1M) for non-fatal stroke, €2016 24k (16k-38k) for myocardial infarction, and €2016 34k (19k-57k) for late preterm birth. The main drivers of the per-case total cost estimates were health outcome severity and societal willingness to pay for risk reduction. Varying the discount rate had the largest effect on preterm birth, with costs changing by ±30% for the discount rates analysed. Recommendation Because stroke, myocardial infarction, and preterm birth have established exposure-response functions linking these to air pollution, cost-benefit analyses should include the costs for these health outcomes in order to adequately guide future air pollution and climate change policies.